Early Vascular Aging in Hypertension - Nilsson, Peter M. (Frontiers in Cardiovascular Medicine, 2020)
With increasing age the cardiovascular risk increases as well as frailty with negative consequences for health such as coronary disease, stroke and vascular dementia. However, this ageing process seems to take a more rapid course in some individuals as reflected in the Early Vascular Ageing (EVA) syndrome that over the recent 10 years has attracted increased attention. The core of EVA syndrome is arterial stiffness in the media layer of large elastic arteries, a process that can be measured by pulse wave velocity, for example along the aorta. Hypertension is a well-known cardiovascular risk factor in its own right, but also linked to the EVA process. However, several studies have shown that also non-hemodynamic factors contribute to arterial stiffness and EVA, such as impaired glucose metabolism, chronic inflammation and oxidative stress. New perspectives have been introduced for linking early life programming affecting newborn babies and birth weight, with later risk of hypertension, arterial stiffness and EVA. New drugs are being developed to treat EVA when lifestyle intervention and conventional risk factor controlling drugs are not enough. Finally, the opposite phenotype of EVA is Healthy Vascular Ageing (HVA) or even Super Normal Vascular Ageing (SUPERNOVA). If protective mechanisms can be found and mapper in these fortunate subjects with a slower than expected ageing process, there could exist a potential to find new drug targets for preventive therapy.